Tumor Lactic Acidosis: Protecting Tumor by Inhibiting Cytotoxic Activity Through Motility Arrest and Bioenergetic Silencing - Fischbeck, Angelika J.; Ruehland, Svenja; Ettinger, Andreas; Paetzold, Kerstin; Masouris, Ilias; Noessner, Elfriede; Mendler, Anna N. (Frontiers in Oncology, 2020)
Adoptive T cell therapy (ACT) is highly effective in the treatment of hematologic malignancies, but shows limited success in solid tumors. Inactivation of T cells in the tumor milieu is a major hurdle to a wider application of ACT. Cytotoxicity is the most relevant activity for tumor eradication. Here we document that cytotoxic T cells (CTL) in lactic acidosis exhibited strongly reduced tumor cell killing, which could be compensated partly by increasing the CTL to tumor cell ratio. Lactic acid intervened at multiple steps of the killing process. Lactic acid repressed the number of CTL that performed lytic granule exocytosis (degranulation) in tumor cell co-culture, and, additionally impaired the quality of the response, as judged by the reduced intensity of degranulation and lower secretion of cytotoxins (perforin, granzyme B, granzyme A). CTL in lactic acid switched to a low bioenergetic profile with an inability to metabolize glucose efficiently. They responded to anti-CD3 stimulation poorly with less extracellular acidification rate (ECAR). This might explain their repressed granule exocytosis activity. Using live cell imaging, we show that CTL in lactic acid have reduced motility, resulting in lower field coverage. Many CTL in lactic acidosis did not make contact with tumor cells; however, those which made contact, adhered to the tumor cell much longer than a CTL in normal medium. Reduced motility together with prolonged contact duration hinders serial killing, a defining feature of killing potency, but also locally confines cytotoxic activity, which helps to reduce the risk of collateral organ damage. These activities define lactic acid as a major signaling molecule able to orchestrate the spatial distribution of CTL inside inflamed tissue, such as cancer, as well as moderating their functional response. Lactic acid intervention and strategies to improve T cell metabolic fitness hold promise to improve the clinical efficacy of T cell-based cancer immunotherapy.